A generalized seismic sliding model of slopes with multiple slip surfaces. (15th April 2021) - Song, Jian; Rodriguez‐Marek, Adrian; Feng, Tugen; Ji, Jian
Abstract: Earthquake‐induced permanent displacements of slopes are generally evaluated through the simplified sliding block analyses of a singular coherent mass on a predefined failure plane. However, coseismic landslides may exhibit multiple slip surfaces as a result of earthquake shaking. This study presents a generalized seismic sliding analysis using a column of sliding blocks to model seismic slope failures with multiple slip surfaces. The formulation of the sliding mode equations of the block system is obtained by a rigorous theoretical derivation. Both a rigid soil column associated with an acceleration–time series that is constant with depth, and a flexible soil column considering an acceleration–time series that varies throughout the sliding mass is presented. The conditional yield accelerations and the equivalent seismic accelerations are defined to characterize the complex interplay of the sliding block assemblies. The approach is applied to model the seismic sliding behavior of layered slopes in which failures would likely occur at the interfaces between soil layers with different shear strengths. The effects of input ground motions and soil deposits on the sliding patterns of slopes are investigated. The developed generalized model provides a promising means for evaluating the seismic slope stability by combining a number of seismic failure locations within slopes.